Intratumoral delivered novel circular mRNA encoding cytokines for immune modulation and cancer therapy - Jiali Yang; Jiafeng Zhu; Jiaojiao Sun; Yiyun Chen; Yaran Du; Yiling Tan; Linpeng Wu; Mengting Zhai; Lixiang Wei; Na Li; Ke Huang; Qiangbo Hou; et al. (Elsevier, 2022)
The success of the two mRNA vaccines developed by Moderna and BioNTech during the COVID-19 pandemic increased research interest into the application of mRNA technologies. Compared with the canonical linear mRNA used in these vaccines, circular mRNA has been found to mediate more potent and durable protein expression and demands a simpler manufacturing procedure. However, the application of circular mRNA is still at the initiation stage, and proof of concept for its use as a future medicine or vaccine is required. In the current study, we established a novel type of circular mRNA, termed cmRNA, based on the echovirus 29-derived internal ribosome entry site element and newly designed homology arms and RNA spacers. Our results demonstrated that this type of circular mRNA could mediate strong and durable expression of various types of proteins, compared with typical linear mRNA. Moreover, for the first time, our study demonstrated that direct intratumoral administration of cmRNA encoding a mixture of cytokines achieved successful modulation of intratumoral and systematic anti-tumor immune responses and enhanced anti-programmed cell death protein 1 (PD-1) antibody-induced tumor repression in a syngeneic mouse model. This novel circular mRNA platform is thereby suitable for direct intratumoral administration for cancer therapy.